Efisiensi Ekonomi Usahatani Padi Lahan Kering di Kabupaten Lampung Selatan - Muhammad Fauzan (Fakultas Pertanian, Universitas Timor, 2020)
Dryland rice farming can be use to increase rice production in order to meet national food needs. To achieve high productivity, dryland rice farming systems must be carried out efficiently so that extra skills are needed from each individual farmer. This study aims to analyze factors that influence the production and economic efficiency level of dryland rice farming in Lampung Selatan Regency. Data collection was conducted by survey method with 60 farmers. The stochastic frontier production function is used in this study for data analysis. The results showed that the factors affecting dry land rice production in Lampung Selatan Regency were land area, seeds, N fertilizer, P fertilizer, solid pesticides, labor, and types of seeds. The average level of technical, allocative, and economic efficiency of dryland rice farming in Lampung Selatan Regency is 0.869; .957; and 0.829. These results indicate that farmers can still improve technical efficiency and allocative efficiency in order to achieve economically efficient conditions.